Embryotoxicity of Copper and Zinc in Tropical Sea Urchin Tripneustes gratilla - Edullantes, Brisneve; Galapate, Ritchelita (Science Diliman: A Journal of Pure and Applied Sciences; Vol 26 No 1 (2014), 2014)
The study determined the individual toxicity of copper (Cu) and zinc (Zn) in sea urchin Tripneustes gratilla . Bioassay using inhibitions on fertilization, early cleavage, mid cleavage, late cleavage and blastulation as endpoints involved exposure of viable gametes to Cu and Zn for 0.5, 3, 6, 9 and 12 h, respectively. Inhibitions increased significantly with concentration of Cu and Zn. Probit analysis estimated EC50 values for Cu and Zn, respectively, at 32 and 67 μg·L-1 on fertilization; 31 and 93 μg·L-1 on early cleavage; 43 and 61 μg·L-1 on mid cleavage; 42 and 42 μg·L-1 on late cleavage; and 20 and 44 μg·L-1 on blastulation. Results showed that toxicity of Cu is significantly higher (p<0.05) than that of Zn in all developmental stages, except in late cleavage. Also, the inhibitions elicited by Cu showed sensitivity to life stages. This study provided evidence on heavy metal species-sensitive, concentration-dependent and stage-specif ic inhibitions on embryonic development in T. gratilla to Cu and Zn. Keywords: Embryotoxicity, sea urchin development, individual toxicity, heavy metals